Online learning experiences from the perspective of Saudi university students: A mixed-methods study on critical success factors - Almalki , Shatha Mohammed (Journal of Education and e-Learning Research, 2025)
This study aimed to explore Saudi university students’ experiences of online learning by understanding the significant factors that affect this learning. A mixed-methods research methodology was employed using an explanatory sequential design in two stages. Quantitative data were first collected via a questionnaire focused on critical success factors (CSFs), followed by the collection of qualitative data from four focus groups and ten interviews. The technical design aspects of the CSFs, namely ‘basic online modality’ and ‘interactive online modality,’ received the highest satisfaction scores in the questionnaire, while the online social comfort factor scored the lowest. The findings highlight a significant need to consider instructional design aspects when planning and implementing online courses, taking into account students’ academic levels and the consistency of the online course content. Teachers need to be trained in teaching strategies that support authentic learning, facilitate students’ online interactions, and maintain a positive atmosphere. This research is essential as it provides an understanding of the current status of online learning from the perspective of Saudi students. It can assist policymakers in the Saudi Ministry of Education to improve online learning by considering CSFs and other contextual factors that influence students’ learning experiences. Additionally, this research has international significance, particularly for developing countries, as it discusses factors affecting students’ online learning experiences. Considering these factors may help improve online learning outcomes in other countries.